2012
DOI: 10.1159/000339640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electroacupuncture on Insulin-Like Growth Factor-I and Oxidative Stress in an Animal Model of Renal Failure-Induced Hypertension

Abstract: Background/Aims: The present study was performed to demonstrate the effect of electroacupuncture (EA) and acupuncture on renal failure (RF)-induced hypertension. Methods: We stimulated the Zusanli (ST36) and Taixi (KI3) acupoints in a rat model of RF-induced hypertension. Results: EA significantly reduced RF-induced hypertension (p < 0.05). In a histopathological study, increments in RF-induced glomerulosclerosis and tubulointerstitial fibrosis were attenuated by EA treatment (p < 0.05). The increase in albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…In the future, we will conduct further studies on the mechanism of long-term efficacy of acupuncture for the treatment of hypertension. Indeed, there are many other valuable acupoints to reduce BP, such as KI3, ST36, or acupoint compatibility [ 6 , 9 , 30 ], which is also one of our future research directions.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we will conduct further studies on the mechanism of long-term efficacy of acupuncture for the treatment of hypertension. Indeed, there are many other valuable acupoints to reduce BP, such as KI3, ST36, or acupoint compatibility [ 6 , 9 , 30 ], which is also one of our future research directions.…”
Section: Discussionmentioning
confidence: 99%
“…Thorsteinsdottir et al [63] indicated that degrading ECM and reducing fibrosis were advantageous to satellite cell migration and differentiation and promoted skeletal muscle regeneration. In organ fibrosis research, electro-acupuncturing the ST36 alleviated renal failure-induced glomerulosclerosis, tubulointerstitial fibrosis [64], and carbon tetrachloride-induced hepatic fibrosis [65]. To investigate whether EA can reduce ECM fibrosis of skeletal muscle after contusion, this study observed the fibrosis formation process in the damaged region repeatedly on days 7, 14, and 28.…”
Section: Discussionmentioning
confidence: 99%
“…However, EA increased these levels significantly more than acupuncture did. 16 EA also increased IGF-1 levels considerably in osteoporotic model rats who had undergone ovariectomy. 17 Meanwhile, laserpuncture at ST 36 and SP 6 increased IGF-1 levels in adolescent rats.…”
Section: Igf-1mentioning
confidence: 84%